An Assessment of Microfinance Institution Services and Performance of Small and Medium Enterprises in Kabale Municipality. - Mugarura, Elijah (Kabale University, 2023)
Performance of Small and Medium Enterprises (SMEs) has been recognized as an important contributor to many global economies. The importance of Small and Medium Enterprises as engines of employment creation and economic growth cannot go unrecognized. However, in the recent years most SMEs continue to register failures within the first few months in operation due to financial literacy problems and resource insufficiencies. Microfinance institutional services have thus been established to bridge the resource needs and capital insufficiency gaps that exist among the SMEs. Literature on how Microfinance Institutional Services affect the Performance of Small and Medium Enterprises (SMEs) remains scanty in Kabale district, South Western Uganda. This study assessed Microfinance Institution Services and Performance of Small and Medium Enterprises in Kabale Municipality. The specific objectives were to assess; effect of provision of financial literacy, development of managerial skills, and marketing facilitation through SME clubs, marketing associations on the performance of small and medium enterprises. The study was descriptive in nature employing quantitative approaches for data collection and analysis. Information was gathered from a sample of 71 different SME owners and other key informants using questionnaire. Data was analyzed using Microsoft EXCEL and SPSS Version 22.0 to generate both descriptive and inferential statistics. The study found out that provision of financial literacy had a positive significant effect on the performance of SMEs. Financial literacy programs like savings literacy, debt literacy and investment literacy supported business owners to safely manage income, expenditure and savings, make clear financial decisions, timely pay back loans as well as investment diversification. all of which improved performance of SMEs. The study also found out that development of managerial skills positively affected SMEs performance mainly by improving SME governance, increasing business vision through met objectives and plans as well as motivating employees to work hard for better hence guaranteeing SMEs ability to compete, survival and thrive in a dynamic environment. The study further confirmed that marketing facilitation through SME Clubs, marketing associations positively affected performance of SMEs. SME Clubs and marketing associations offered personal liability protection, business security, access to capital and resources, created a less competitive business environment, contributed to business networking and offered a collective voice for small business owners. In conclusion, the study further confirmed that microfinance institution services (financial literacy, development of managerial skills and marketing facilitation) positively influenced performance of SMEs and recommended that more managerial trainings should be given to the SMEs by the MFI so as to equip them with more knowledge on running their enterprise which would translate into better management of funds and enhance performance in a long run. The study further recommends MFI to lower on their interest rates put on loans they give to SMEs so as not to let loans be too heavy for them to pay back which may hamper their positive contributions on the growth of SMEs. SME owners need more training in programs like budgeting and planning, debt management, record keeping, saving and retirement plans.